METHODS OF SYSTEM ANALYSIS AND MODELS FOR SOLVING PROBLEMS OF THE EFFICIENT ENVIRONMENTAL RESOURCE MANAGEMENT AND ECOLOGICAL MANAGEMENT BASED ON REMOTELY SENSED DATA AND IN-SITU MEASUREMENTS (BASED ON THE PUBLICATION OF THE DEPARTMENT OF SYSTEM ANALYSIS O - Федоровский, А. Д.; Якимчук, В. Г.; Соколовская, А. В. (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2015)
The possibility of using methods of system analysis and model of using remotely sensed data and in-situ measurements for solving problems of the efficient environmental resource management and ecological management is substantiated. The results of adaptation, modification, development and using of the next methods are shown: multiobjective optimization method, analytic hierarchy process, method of spectral autocorrelation, method of structural and textural analysis, Kolmogorov’s spatial interpolation method, fractal analysis mathod, system dynamics method, influences balance-based adaptive method, multiple regression method.